Social fragmentation of urban space - Gonçalves Vieira, Sidney (Universidad Católica de Pereira, 2012)
“ESPACIO PÚBLICO Y CIUDADANÌA” it is a very valid proposal, because it allows us to discuss the production of the urban space in a forum dedicated to the analysis and to remit it to the established relationships between the society and the space. Such relationships, views under the materialistic and dialectical logic and based in a critical posture of reading of the reality, appears in a very clear way. Understanding this way with more easiness the use and the appropriation of the space, evidencing the production of a space where the encounter among public and private it provides the exclusion and social fragmentation of the space.